Preoperative lymphocyte count, neutrophil to lymphocyte and platelet to lymphocyte ratio predict the recurrence with progression and cancerization in vocal fold lesions—retrospective study - Rzepakowska, Anna; Pietruszewska, Wioletta; Żurek, Michał; Molga-Magusiak, Maria; Leszczyński, Michał; Niemczyk, Kazimierz (PeerJ, 2023)
Backgrounds This study explored the contribution of peripheral blood markers in diagnosis and prognosis estimation of different stages of laryngeal dysplasia and early glottic cancer. Methods Retrospective analysis of clinical, histopathological and laboratory data of 220 patients including hemoglobin, neutrophil, lymphocyte, monocyte and platelet counts, neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR). Results The mean hemoglobin level and platelets count showed differences between histopathological stages of lesions (p = 0.041 and 0.046, respectively). In patients with recurrent lesions mean level of lymphocyte count, NLR and PLR were significant in assessing progression and cancerization (p = 0.005, 0.028 and 0.023, respectively). The univariate analysis recognized level of PLR ≥ 141.74 as significant risk factor of the recurrence of vocal fold hypertrophic lesions (OR = 1.963). Conclusions The levels of blood cells and their ratios seem to be effective in predicting the recurrence of lesion and even more their potential role in indicating malignant progression.
Keywords: Laryngeal cancer; Laryngeal dysplasia; Lymphocyte count; Neutrophil count; Neutrophil to lymphocyte ratio; Blood markers